Men and Their Dogs 2016
DOI: 10.1007/978-3-319-30097-9_3
|View full text |Cite
|
Sign up to set email alerts
|

A New Understanding of Man’s Best Friend: A Proposed Contextual Model for the Exploration of Human–Animal Interaction Among Insecurely Attached Males

Abstract: My own (Chris Blazina) interest in the bond between man and dog is longstanding, tracing its origins to my youth. When my family's little house was filled with ten or more people, and felt particularly cramped, I would take a seat on the back steps and talk things over with our gentle German shepherd. I remember him sitting very still, alert, and attentive, almost like he was on point, but with a much calmer demeanor. As I recounted sometimes the frustrating events occurring on the other side of the brick wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
0
2
0
1
Order By: Relevance
“…It has been suggested that the bond with an animal companion may play a significant role in helping those across the life span develop relational attitudes and skillsets [1,7,8]. Part of the rationale for the generative nature of human-animal interaction [9] is based on the recent focus of individuals having competing attachment models operating within one's attachment repertoire [10]. That is, instead of a single global attachment orientation (i.e., secure or insecure) we may have a series of competing/ divergent person/context-specific ones.…”
Section: Hierarchical Structuring Of Attachment Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the bond with an animal companion may play a significant role in helping those across the life span develop relational attitudes and skillsets [1,7,8]. Part of the rationale for the generative nature of human-animal interaction [9] is based on the recent focus of individuals having competing attachment models operating within one's attachment repertoire [10]. That is, instead of a single global attachment orientation (i.e., secure or insecure) we may have a series of competing/ divergent person/context-specific ones.…”
Section: Hierarchical Structuring Of Attachment Figuresmentioning
confidence: 99%
“…Attachment findings have additional implications for human-animal interaction. While there has been some support for a generalization of insecure attachment behaviors from human companions to animal companions, [4,12] it has also been suggested many may find a different or even corrective experience among canine companions [9]. Those with an insecure attachment style among human dyads may find a respite from these conflicts in relationships with animal companions.…”
Section: Hierarchical Structuring Of Attachment Figuresmentioning
confidence: 99%
“…Totodată, studiile indică o incidență în creștere la nivelul cazurilor de tulburare de spectru autist, de la un caz la 2500 cu 25 de ani în urmă, până la unul la Luând în considerare teoriile referitoare la relația om -animal precum cea a biofiliei (tendința oamenilor de a realiza conexiuni cu alte ființe vii, Kellert & Wilson, 1995) și a atașamentului (conexiunea bidirecțională ce se stabilește între oameni și animale, Amiot & Bastian, 2015), precum și fundamentul autonom și neuroendocrin ce stă la baza consecințelor interacțiunii dintre oameni și celelalte specii care contribuie la dezvoltarea funcțiilor executive și de adaptabilitate (Carter & Porges, 2016;Ling, Kelly, & Diamond, 2016;Blazina, O'Neil, & Denke, 2016;Gee et al, 2017), cercetătorii și-au concentrat atenția asupra studiului posibilității implementării terapiei asistate de animale. Dat fiind faptul că printre primele animale utilizate pentru relaxare, sau pentru a îmbunătăți starea de spirit a celor cu boli incurabile în Grecia Antică prin plimbări și alte activități, erau caii (Bizub, Joy, & Davidson, 2003), dar și datorită caracterului plăcut și distractiv al interacțiunii copiilor cu aceste animale, terapia asistată de cai a reprezentat o potențială formă de ameliorare a simptomelor din spectrul autist.…”
Section: Obiectivele Terapiei Facilitate De Caiunclassified